Предлагаю заменить
Тогда:
Получаем
p=- 5; p=4.
р>0 => p=4
Перейдем к начальной системе:
Решим второе уравнение системы:
- по Т.Виета
Отсюда, подставляя получаем:
Предлагаю заменить![\sqrt{(x+y)}=p0](/tpl/images/0092/7710/a06a5.png)
Тогда:![p^2+p=20; \ \ \ p^2+p-20=0; \ \ \ (p+5)(p-4)=0](/tpl/images/0092/7710/ca75b.png)
Получаем
p=- 5; p=4.
р>0 => p=4
Перейдем к начальной системе:![\left \{ {{\sqrt{(x+y)}=4} \atop {x^2+y^2=136}} \right\ \ \ <= \left \{ {{x+y}=16} \atop {x^2+y^2=136}} \right<=](/tpl/images/0092/7710/20523.png)
Решим второе уравнение системы:
Отсюда, подставляя получаем:
![\left \{ {{x}=16-y} \atop {y=6}} \right\ \ <=\left \{ {{x}=10} \atop {(y=6}} \right](/tpl/images/0092/7710/f625b.png)
ОТВЕТ: (6;10); (10; 6)